A NEW MANAGERIAL TOOL FOR SCENARIOS IN SCHEDULING - GEORGE CRISTIAN GRUIA; MICHAL KAVAN (Global Economic Observer)
The purpose of this paper is to introduce a newly developed managerial tool, Quality Scheduling Index (QSI), which can be used at the improvement of quality and time consumption within not only manufacturing companies. The authors present this tool as a result of the actual market conditions of finding a way for managing and controlling the usage of time, quality of work and the costs associated with these two factors. The paper is focused on the area of Management of Production and Operations with the main goal of developing the area of scheduling research and main purpose of increasing the productivity of a manufacturing enterprise by using at maximum the available resources, without any additional costs or investments. A survey is realized regarding the market requirements and partial empirical results of the authors’ researches are presented, with conclusions being drawn for future studies. A scenario mainframe is also developed and a relation between QSI and scenarios is presented. The paper represents partial results of the grant projects GAČR P403/12/1950 and SGS13/191/OHK2/3T/12.